ANALISIS LINGUISTIK PRINSIP KERJA SAMA DALAM TUTURAN CERITA HUMOR NAWADIR JUHA LI AL-ATHFAL - Ulam, Asyifa; Emzir, Emzir; Nuruddin, Nuruddin (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2018)
The purpose of this study was to describe (1) the compliances and deviations of the principle of cooperation in the speech of Arabian humorous story